Insolvency and reform of English bankruptcy law, 1831-1914 - Lester, V; Lester, V. M. (1991)
This thesis is a history of the reform of English bankruptcy law 1831-1914 and a statistical analysis of the insolvency the reforms sought to limit. The first two chapters describe the historiography of government growth in nineteenth-century Britain and outline the history of English bankruptcy legislation until 1831. Using statistics from bankruptcy reports published by the Board of Trade after 1883 and returns issued by other government entities prior to that date, chapters three and four define the extent and the characteristics of insolvency. These chapters analyze the aggregate level of bankruptcy in particular occupations and geographic areas; they also examine the effect of trade cycles on bankruptcy levels, both in terms of numbers of bankruptcies and losses occasioned. The remaining chapters trace the history of bankruptcy legislation and examine why Parliament embraced the concept of government supervision of bankrupt estates in 1831, then dismantled the system in the 1860s, only to reimpose it once again a short time later. The roles of three groups in this story -- the business community, the legal profession, and the government -- are examined in detail using the records of the local chambers of commerce, law societies, and other organizations. The thesis concludes that, while the aggregate level of losses declined after the Bankruptcy Act of 1883, the loss rates for some occupations did not reflect this decline. Also, trade cycles did not uniformly affect the rate of bankruptcy for all occupations and geographic areas. Random factors rather than trade cycles had the greatest effect on annual bankruptcy rates. The thesis also argues that the extension of government brought about by bankruptcy reforms was largely a pragmatic attempt to manage bankrupt estates efficiently and had little philosophical basis. Further, the close resemblances between bankruptcy reforms and other Victorian extensions of government add to the evidence that, while there may not be a strict pattern to government growth, such growth may be considered as a distinct and identifiable process.